Molecular imaging of HER2 receptor: Targeting HER2 for imaging and therapy in nuclear medicine - Miladinova, Daniela (Frontiers in Molecular Biosciences, 2023)
Targeting HER 2 for imaging and therapy in nuclear medicine has been used with a special emphasis on developing more powerful radiopharmaceuticals. Zirconium-89 plays an essential role in immune PET imaging so was used labeled with anti-HER2 antibody (Trastuzumab and Pertuzumab). Also there were attempts with other PET tracers as Cuprum-64 and Galium-68, as well as SPECT radiopharmaceuticals Indium-111 and Technetium- 99m. Regarding antibody pharmacokinetic that is not quite appropriate for imaging acquisition, several smaller molecules with shorter residence times have been developed. These molecules called nanobody, affibody, minibody do not compromize HER2 receptor affinity and specificity. Excess of trastuzumab do not block the affinity of labeled affibodies. Silica nanoparticles have been conjugated to anti-HER2 antibodies to enable targeting of HER2 expressing cells with potential of drug delivery carry for antitumor agents and beta or alfa emitting radioisotopes commonly used for radionuclide therapy, as Iodine-131, Lutetium-177, Yttrium-90, Rhenium-188 and Thorium-277 .